search
Log In
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
1 vote
75 views

$ \ Sin^{-1}\left [ \frac{3}{5} \right ] + \tan^{-1}\left [ \frac{1}{7} \right ]=$

  1. $\frac{\pi }{4}$
  2. $\frac{\pi }{2}$
  3. $ \ Cos^ {-1} \frac{4}{5} $
  4. $\pi$
in Quantitative Aptitude 9.3k points 31 523 813
recategorized by
75 views

1 Answer

0 votes
$\textrm{let us assume $sin^{-1}(\frac{3}{5})=\theta$}$

$\implies$ $\sin\theta=\frac{3}{5}$

$\because \sin\theta=\frac{perpendicular}{base}$

$\textrm{by using pythagoras theorem we can find the base of right angle triangle }$

$\implies$ $H^2=B^2+P^2$

$\textrm{base =4}$

$\therefore$ $\tan\theta=\frac{perpendicular}{base}$

$\implies$ $\tan\theta=\frac{3}{4}$

$\implies$ $\theta=\tan^{-1}\frac{3}{4}$

$\therefore$ $tan^{-1}\frac{3}{4}+tan^{-1}\frac{1}{7}$

$\because \tan^{-1}(A+B)=tan^{-1}(\frac{A+B}{1-AB})$

$\implies$ $\tan^{-1}(\frac{\frac{3}{4}+\frac{1}{7}}{1-\frac{3}{4}*\frac{1}{7}})$

$\implies$ $tan^{-1}(1)$

$\because tan^{-1}(1)=\frac{\pi}{4}$

$\textrm{option A is correct.}$
3.5k points 4 10 63

Related questions

0 votes
1 answer
1
88 views
If $ \ Sinx+Sin^{2} x=1$ then $ \ Cos^{8}x+ 2 \ Cos^{6} x+ \ Cos^{4} x$ equals to : $0$ $-1$ $1$ $2$
asked Apr 3, 2020 in Quantitative Aptitude Lakshman Patel RJIT 9.3k points 31 523 813 88 views
1 vote
1 answer
2
125 views
If $\theta$ is an acute angle and $\tan\theta+\cot\theta =2$, Find the value of $\tan ^{7}\theta +\cot ^{7}\theta$. $-2$ $1$ $2$ $0$
asked Apr 1, 2020 in Quantitative Aptitude Lakshman Patel RJIT 9.3k points 31 523 813 125 views
0 votes
0 answers
3
88 views
If $x=\cos1^{\circ} \cdot \cos2^{\circ} \cdot \cos3^{\circ}\dots\cos89^{\circ}$ and $y=\cos2^{\circ}\cos6^{\circ}\cos10^{\circ}\dots\cos86^{\circ}$ then what the integer is nearest to $\dfrac{2}{7}\log _{2} \left( \dfrac{y}{x}\right )$is: $19$ $17$ $15$ $21$
asked Apr 1, 2020 in Quantitative Aptitude Lakshman Patel RJIT 9.3k points 31 523 813 88 views
0 votes
1 answer
4
103 views
The expressions $\dfrac{\tan A}{1-\cot A}+\dfrac{\cot A}{1-\tan A}$ can be written as: $\sin A \ \cos A+1$ $\sec A \ cosec A+1$ $\tan A+ \cot A+1$ $\sec A +cosec A$
asked Apr 1, 2020 in Quantitative Aptitude Lakshman Patel RJIT 9.3k points 31 523 813 103 views
1 vote
1 answer
5
102 views
If $cosec\theta-\sin\theta=1$ and $\sec\theta-\cos\theta=m$, then $l^{2}m^{2}(l^{2}+m^{2}+3)$ equals to: $1$ $2$ $2 \sin\theta$ $\sin\theta \cos\theta$
asked Apr 1, 2020 in Quantitative Aptitude Lakshman Patel RJIT 9.3k points 31 523 813 102 views
...